Marketing Research: History of Industry Development - D. G. Tsybikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article deals with study of institutionalization of marketing research in the US. Three stages of history of this process were identified: birth of industry (1880–1900-s), when first marketing research were registered of advert agencies and academic scientists; development (1920–1920-s), i. e. the period of setting up research departments in different organizations and specialized research companies, which is characterized by piling-up the pool of professional publications and setting-up first professional associations; formalizing (1930–1940-s), when market research became an ordinary business-practice and inside the research corps a serious methodological breakthrough took place, which determines current standards and practices of research activities. The author mentioned prominent figures in the field of marketing research on each stage, whose contribution to the development of industry allows us to call them The Founders. A conclusion was made about the crucial importance of the idea of scientific marketing for the development of industry. Attracting representatives of academic community (psychologists, sociologists, economists, etc.) raised the quality and efficiency of marketing research and legitimize its status in business-practice.